Opposites in Reasoning Processes: Do We Use Them More Than We Think, but Less Than We Could? - Branchini, Erika; Capitani, Elena; Burro, Roberto; Savardi, Ugo; Bianchi, Ivana (Frontiers in Psychology, 2021)
Our aim in this paper is to contribute towards acknowledging the general role of opposites as an organizing principle in the human mind. We support this claim in relation to human reasoning by collecting evidence from various studies which shows that “thinking in opposites” is not only involved in formal logical thinking, but can also be applied in both deductive and inductive reasoning, as well as in problem solving. We also describe the results of a series of studies which, although they have been developed within a number of different theoretical frameworks based on various methodologies, all demonstrate that giving hints or training reasoners to think in terms of opposites improves their performance in tasks in which spontaneous thinking may lead to classic biases and impasses. Since we all possess an intuitive idea of what opposites are, prompting people to “think in opposites” is something which is undoubtedly within everyone’s reach and in the final section, we discuss the potential of this strategy and suggest possible future research directions of systematic testing the benefits that might arise from the use of this technique in contexts beyond those tested thus far. Ascertaining the conditions in which reasoners might benefit will also help in terms of clarifying the underlying mechanisms from the point of view, for instance, of analytical, conscious processing versus automatic, unconscious processing.